Cultural Review of Student Compliance in The Western Region of Indonesia to Health Protocols - Sepriandison Saragih (Universitas Pendidikan Ganesha, 2022)
Health protocols help prevent the transmission of Corona Virus (COVID-19), but the culture of people's adherence to the Covid-19 health protocol in each region is uneven, which is due to the influence of local culture in various blood areas in Indonesia. This study is intended to describe the impact of a culture of adherence to health protocols during a pandemic on students in the Western Indonesia Region. The research approach is quantitative with the type of correlation research, through purposive random sampling, namely 268 students of the Faculty of Teacher Training and Education HKBP Nommensen Pematangsiantar University class of 2018 and 266 students of Faculty of Teacher Training and Education (FKIP) University UHKBPNP class 2019, a total of 534 samples. The data collection instrument used a questionnaire, the data analysis technique used the Kendall's Taub test. The results obtained a significance value of 0.018 <0.05, that there is a relationship between the cultural variables of adherence to health protocols. The correlation coefficient value is 0.554, that the level of relationship between the cultural variables of adherence to health protocols during the pandemic is strong. The direction of the relationship between variables has a positive value of 0.554. Shows the level of obedience culture experienced by students of the Faculty of Teacher Training and Education class 2018 at HKBP Nommensen Pematangsiantar University and students of the Faculty of Teacher Training and Education batch 2019 at HKBP Nommensen Pematangsiantar University based on health protocols.